Current-Cost Financial Statements and Common-Stock Investments Decisions. - McIntyre, Edward V. (The Accounting Review, 1973)
This article presents information on an experiment designed to test the usefulness of an alternative accounting model to one group of users, investors in common stock. The particular model tested calls for general price-level adjustments as well as restatement of accounts to current replacement costs. Subjects were given financial statements of actual companies and were asked to specify a holding period of one, two, or three years and then select the firm which they felt would produce the highest rate of return to the investor during this period. The subjects could also indicate that the company selected would be the same regardless of whether the holding period was one, two, or three years. In addition, subjects were asked to express a measure of the confidence they had in their choices and to place a hypothetical value on the price of the companies stocks. The results were then analyzed considering both the company and the holding period selected to see if subjects using current-cost financial statements made different and better decisions than those using only historical cost financial statements.